What Problem Do Intermediaries Solve? Evidence From Real Estate Markets - Aiello, Darren; Garmaise, Mark; Nadauld, Taylor (Review of Financial Studies, 2026)
We study intermediation in the housing market. Using data from an online platform utilized by real estate agents to generate leads, we identify exogenous intermediary attention arising from the quasi-randomized ordering of potential listings. Greater intermediary attention leads to an increased probability of listing with an agent and selling quickly, and a higher transaction price. The listing and transaction probabilities of neighboring properties decrease in intermediary attention. These results contrast sharply with endogenous correlations and provide causal evidence that intermediaries resolve property-level frictions deriving from search, information, or behavioral considerations but do not mitigate neighborhood-level information asymmetries.